The Jewish Theme in Theophanes the Confessor’s Testimony on the Prophet Muḥammad - Cecota, Błażej (Studia Ceranea, 2023)
Theophanes’ account regarding the rise of Islam and the history of the Prophet Muḥammad appears to be the most detailed and precise one that can be found in Byzantine historiography. The Confessor’s aim was to reproduce as many details about Muḥammad’s life as possible. Since his focus was not on religious ideas, but on key events surrounding the rise of the new religion, his account is not predominantly concerned with discussing Islam’s ideology. However, this does not allow us to regard it as in any way objective. Some of the views it contains were included with the clear goal of discrediting Islam as a religion that rivalled Christianity. This, for example, can be said of Theophanes’ remarks about the relationship between Muḥammad and the Jews. In this article, I focus on this aspect of Theophanes’ account, discussing it in the context of the long-running (the last several decades) scholarly debates regarding Jewish-Muslim relations.